Peningkatan Minat dan Hasil Belajar Siswa Sekolah Dasar melalui Model Pembelajaran Teams Games Tournament Berbantuan Wordwall - Rahayu, Kiswari Puji; Amananda, Novalia; Amalia, Heny (YASIN, 2025)
This study aims to determine the increase in interest and learning outcomes in mathematics basic multiplication material using the Team Games Tournament (TGT) model assisted by wordwall in grade V students of SDN Kepatihan. This type of research is Classroom Action Research (PTK) using the Kimmis and Mc Taggart model. The research subjects consisted of 24 fifth grade students of SDN Kepatihan. Data was obtained using questionnaire and test methods. The results showed that students' interest in learning in the pre-cycle amounted to 62, 93% (quite high), cycle I amounted to 70, 63% (high), cycle II amounted to 82, 92% (very high). Meanwhile, students' learning outcomes are seen from the classical learning completeness or the number of students achieving KKTP. Learning outcomes in the pre-cycle amounted to 68, 71% (14 students reached KKTP), cycle I increased to 78, 81% (17 students reached KKTP), and cycle II increased to 86, 41% (19 students reached KKTP). In the process, it shows that the quality of the learning process has improved, students are more active, communicative, confident and the learning atmosphere is more fun. It can be concluded that the Team Games Tournament (TGT) model with the help of wordwall can increase the interest and learning outcomes of fifth grade mathematics at SDN Kepatihan.